Stock market wealth, housing wealth and consumption: evidence from emerging asian countries - Au, Alicia De-Yu (2010)
The purpose of this study is to investigate the effects of stock market wealth and housing wealth on private consumption in 6 emerging Asian countries. It estimates a base-case error-correction model containing private consumption, disposable income, stock market wealth, and housing wealth using quarterly observations for the period 1999:1-2009:4. The findings are such that, in the long run, there is no evidence of stock market wealth effect on private consumption in most of the countries, with the exception of Singapore and Taiwan, while there is strong evidence of housing wealth effect on private consumption across all of the countries. In the contrary, in the short run, both stock market wealth and housing wealth have no effect on private consumption in most of the countries, except for Hong Kong where the housing wealth effect is statistically significant. Overall, housing prices should warrant a closer monitoring by policy makers as compared to stock prices, seeing that there exists the possibility of large changes in housing price to cause distress through the uncertainty in consumption behavior.